2016
DOI: 10.3892/mco.2016.1015
|View full text |Cite
|
Sign up to set email alerts
|

Muscle wasting associated with the long-term use of mTOR inhibitors

Abstract: Some targeted therapies alter muscle mass due to interference with pathways of muscle metabolism. The effects of mammalian target of ra pamycin (mTOR) inhibitors on muscle mass have yet to be fully elucidated. In the present study, the computerized tomography (CT) scans of patients receiving mTOR inhibitors for at least 6 months taken at baseline and post-therapy were retrospectively retrieved, and body composition analyses were performed using the software, sliceOmatic version 5.0 (TomoVision, Inc., Magog, QC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(41 citation statements)
references
References 21 publications
(40 reference statements)
2
37
1
Order By: Relevance
“…First, encouraging mTOR and AKT signaling to overcome sarcopenia with adalimumab, silver linings on the horizon by Ebner & Haehling, (42) is recommended since long-term use of mTOR inhibitors led to a marked loss of muscle mass. (43) As summarized by several investigators (44)(45)(46) and ours in the current study ( Fig. 6), molecular substrates and mechanisms underlying the dysregulation of skeletal muscle synthesis and degradation included proinflammatory cytokines such as TNF-a, IL-1, IL-6 and related signaling transduction systems such as NF-kB, MAPKs, acute phase reactants, and myostatin-activin-SMAD pathways.…”
Section: Discussionsupporting
confidence: 55%
“…First, encouraging mTOR and AKT signaling to overcome sarcopenia with adalimumab, silver linings on the horizon by Ebner & Haehling, (42) is recommended since long-term use of mTOR inhibitors led to a marked loss of muscle mass. (43) As summarized by several investigators (44)(45)(46) and ours in the current study ( Fig. 6), molecular substrates and mechanisms underlying the dysregulation of skeletal muscle synthesis and degradation included proinflammatory cytokines such as TNF-a, IL-1, IL-6 and related signaling transduction systems such as NF-kB, MAPKs, acute phase reactants, and myostatin-activin-SMAD pathways.…”
Section: Discussionsupporting
confidence: 55%
“…Several studies showed that the decrease of LBM is associated with higher chemotherapy toxicities, as well as a worse outcome in various cancer type [ 5 , 15 40 ]. Moreover, a muscle wasting without adipose tissue and body weight reduction was observed during anticancer treatment with both chemotherapy and target therapy [ 25 , 41 ]. Focusing on studies conducted on breast cancer, Prado and colleagues published a study performed on 55 metastatic patients treated with capecitabine, evaluating muscle mass by CT scans at L3 vertebra level.…”
Section: Discussionmentioning
confidence: 99%
“…Targeting mTORC1 signalling is the only therapeutic avenue yet explored for laminopathies that has promise against both dystrophic and progeroid laminopathies [137], but it has yet to be tested in sarcopenia. However, as a note of caution, patients taking rapamycin for more than 6 months for treatment of renal cell carcinoma or paracrine neuroendocrine tumours demonstrated an increase in sarcopenia [138], a worrying finding as sarcopenia is predictive of outcomes in cancer patients. Longitudinal rapamycin studies in healthy subjects, such as those ongoing in companion dogs [139] are needed to inform on whether low dose mTOR inhibition may be able to delay or even prevent the onset of sarcopenia.…”
Section: Musculoskeletal Disorders 251 Sarcopenia and Muscle Wastingmentioning
confidence: 99%